Efficiency Analysis of Maize Farming Around the Buffer Areas of The Mandalika Special Economic Zone (SEZ), Central Lombok: A Stochastic Frontier Analysis Approach - Sarlan, Muhamad; Ihsan, Sahrul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Central Lombok Regency has great potential for corn development, although its production decreased from 84,650 tons in 2020 to 53,000 tons in 2023. The presence of the Mandalika Special Economic Zone (SEZ) and the World Bank’s I-Core program creates opportunities for agricultural development, marketing, and improvement of infrastructure and regional economic support. This study aims to analyze the factors influencing corn production, measure technical, allocative, and economic efficiency, and identify the factors contributing to technical, allocative, and economic inefficiency. The research employed a quantitative descriptive-analytical method with a Stochastic Frontier Analysis (SFA) approach using the Maximum Likelihood Estimation (MLE) method. The research locations were purposively selected in three villages surrounding the Mandalika SEZ, namely Rambitan, Mujur, and Penujak, with 90 farmer respondents selected through simple random sampling. The results show that land area, labor, and herbicides significantly affect corn production, while seeds, urea fertilizer, and Phonska fertilizer have positive but insignificant effects. In general, corn farmers in Central Lombok are technically efficient but not yet allocatively and economically efficient. Socioeconomic factors that increase technical inefficiency include age, farming experience, farmer group participation, and credit access, while education level and household size reduce it. Allocative inefficiency is influenced by farm distance, whereas economic inefficiency increases with credit access and decreases with farmer group participation and household size